STUDI BIBLIKA TENTANG HIDUP KUDUS MENURUT EFESUS 4:17-32 DAN IMPLIKASINYA BAGI PEMUDA GUPDI TANGGUL - Hardin Jaya Putra Lase (Sekolah Tinggi Teologi Duta Panisal, 2020)
Holy life is a command of God for those who live in him, but in reality there are many people who live in Christ but do not maintain their holy life properly, including todays youth whose lives are bound by sin. Youth is a very important and valuable time. If someone goes through his youth with failure in terms of maintaining his holy life, then it is likely to experience failure in the next journey of life. Conversely, if his youth is filled with how to maintain a holy life, then success will follow throughout his life. Therefore the purpose of this writing is;first, that todays youth fully understand Gods commandment about living a holy life and applying it ini his daily life;the second analyzes biblically about the holy life, both in the context of the Old Testament, the New Testament and according to Ephesians 4:17-32; third, know the theological and practical implications of living a holy life based on Ephesians 4:17-32. This research was conducted with a qualitative method with the conclusion that the holy life of a person must be maintained so that he has a good life and always pleases God.